Individual and Collective Posttraumatic Growth in Victims of Natural Disasters: A Multidimensional Perspective. Issue 5 (4th July 2017) - Wlodarczyk, Anna; Basabe, Nekane; Páez, Dario; Villagrán, Loreto; Reyes, Carlos
ABSTRACT: This study set out to incorporate the collective dimensions of posttraumatic growth and examined the construct and predictive validity of The Individual and Collective Posttraumatic Growth Scale (ICPTGS) . Participants were 332 volunteers who had experienced the earthquake on February 27, 2010, in Chile. Analysis allowed us to confirm a multidimensional structure composed of four dimensions: individual, spiritual, communal growth, and societal growth . Additionally, we identified association among ICPTGS, perceived emotional impact, and social well-being. This study emphasizes that positive changes resulting from the exposure to collective disasters can be perceived also at the collective or community level.